2009
DOI: 10.1111/j.1439-0396.2008.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of colic in horses in Austria

Abstract: A hospital-based case study was conducted at the University of Veterinary Medicine Vienna for a 1-year period. The purpose of this study was to determine possible alterable and non-alterable risk factors of equine colic in Austria. The investigated parameters were obtained from hospital medical records (individual factors, duty of the horse, deworming, change in diet and water intake), from questionnaires (feed intake, watering types, housing and pasture practices) and from http://www.orf.at (weather-related f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 24 publications
3
29
0
Order By: Relevance
“…As expected the HB diet induced changes in the microbial hindgut ecosystem: we found an increase of colonic total anaerobic bacteria, lactate-utilizing bacteria 0,0E+00 and amylolytic bacteria concentrations in accordance with data previously reported with such diets [5][6][7]. These microbial disturbances occurring in the hindgut might be responsible for digestive upsets [31] and induce intestinal pain in animals [2,32]. However no symptoms of colic were noticed along the experimental trial.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As expected the HB diet induced changes in the microbial hindgut ecosystem: we found an increase of colonic total anaerobic bacteria, lactate-utilizing bacteria 0,0E+00 and amylolytic bacteria concentrations in accordance with data previously reported with such diets [5][6][7]. These microbial disturbances occurring in the hindgut might be responsible for digestive upsets [31] and induce intestinal pain in animals [2,32]. However no symptoms of colic were noticed along the experimental trial.…”
Section: Discussionsupporting
confidence: 92%
“…However, the domestication and the use of horses as athletes have led managers to feed them large meals of low-fiber and usually high-starch diets in order to provide more energy. Epidemiological studies reported that the ingestion of a large amount of concentrate or cereals, and therefore starch, induced intestinal pain and strongly increased the risk of colic [2][3][4]. Moreover several studies showed that high intake of starch created disturbances in the equine large intestine ecosystem, not only in terms of its composition but also …”
Section: Introductionmentioning
confidence: 98%
“…The consumption of 2.5-5.0 kg of concentrates daily was shown to increase the risk of suffering colic by almost 5 times in one study (Tinker et al 1997), whilst a separate study found a similar quantity of oats to be associated with almost 6 times more colic episodes (Hudson et al 2001). It has been suggested that pelleted-, extruded-or sweet-feeds may pose a greater risk than whole grains (Morris et al 1989, Tinker et al 1997 although this is disputed by other studies (Cohen et al 1999, Kaya et al 2009, Little & Blikslager 2002. Studies of racing Thoroughbreds (Richards et al 2006, Southwood et al 1993 indicating that an increased incidence of colic is expected as an occupational hazard of competitive racing.…”
Section: Risk-factors For Colic In Generalmentioning
confidence: 93%
“…35.1, Table 35-3a) (Hudson et al 2001, Kaya et al 2009, Tinker et al 1997. Such feeding practices are frequently associated with further potential colic risk-factors such as suboptimal forage intake, high levels of exercise, particular breeds of horses and perhaps restricted turnout although multivariate analysis has been applied in several studies to specifically identify causal factors ( Fig.…”
Section: Risk-factors For Colic In Generalmentioning
confidence: 99%
See 1 more Smart Citation